EVALUATION OF USER SATISFACTION WITH THE HIVISITSCREEN WEBSITE AS AN EDUCATIONAL MEDIUM TO IMPROVE HIV LITERACY AND REDUCE STUDENT STIGMA TOWARD PEOPLE LIVING WITH HIV (PLHIV) - Nirwanto K. Rahim; Ayu Rofia Nurfadhilah; Erwin Purwanto (PT. Jurnal Center Indonesia Publisher, 2025)
HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immunodeficiency Syndrome) remain a global public health crisis, with the increasing number of cases in Indonesia, including Gorontalo, indicating a lack of public knowledge and high social stigma as major obstacles. Advances in information technology offer significant opportunities for health promotion. HiVisitScreen is a modern, website-based digital platform developed as an educational medium to provide up-to-date information on HIV/AIDS, facilitate safe and confidential health access, and reduce the spread of HIV. This descriptive quantitative study, using a cross-sectional design, aimed to describe user satisfaction with the HiVisitScreen website among 150 active students at Gorontalo State University (UNG). User satisfaction was measured using the 13-item End User Computing Satisfaction (EUCS) questionnaire. The results show that overall, users were satisfied with the HiVisitScreen website, with a total mean score of 3.45 (Satisfied category). Among the five EUCS dimensions, Ease of Use had the highest mean score of 3.51 (Highly Satisfied category), emphasizing the application's user-friendliness and accessibility. Meanwhile, the Content dimension received the lowest mean score of 3.40 (Satisfied category), indicating that while the information is relevant and clear, improvements are needed in the completeness and suitability of the content to specific user needs, supporting the plan to add prevention features for serodiscordant couples. The HiVisitScreen website has successfully met user expectations and has the potential to function as an effective website-based intervention in HIV case management within the campus environment.